Efficient and Stable Electrocatalytic Oxygen Evolution from MoTex/Ni(OH)2 Heterostructures - Han, Junhwi; Nam, Myeong Kyun; Shin, Seunghun; Cho, Iaan; Jeon, Hotae; Heo, Jaewon; Lee, Jaehyun; Cho, Min Kyung; Preston, Daniel J.; Hersam, Mark C.; Kim, In Soo; Shong, Bonggeun; et al. (American Chemical Society, 2025)
A design methodology is presented here for MoTex/Ni(OH)2 heterostructured catalysts that enhance the oxygen evolution reaction (OER) in water electrolysis. This approach relies on the transfer of mechanically exfoliated MoTe2 nanosheets to Au/Si substrates followed by electrochemical Te dissolution to induce defect-mediated, partial semiconducting (2H) to metallic (1T’) phase transitions. Immersing the resulting MoTex into a nickel nitrate hydrate solution results in a heterostructure consisting of 2H-MoTex/Ni(OH)2 and 1T’-MoTex/Ni(OH)2 domains, which enables high stability and improved efficiency for the OER compared to IrOx. Both machine-learning potential and density functional theory calculations searched and evaluated all atomic sites for this materials system, thus revealing the enhancement mechanisms of OER via four-electron transfer processes with lowered free energy barriers in the rate-determining steps.